If x = -2 and y = -4, then:
2x - (2x² - 4y)
= 2(-2) - [2(-2)² - 4(-4)]
= -4 - [2(4) - 16]
= -4 - [8 - 16]
= -4 - (-8)
= -4 + 8
= 4
So, the value of 2x - (2x² - 4y) when x = -2 and y = -4 is 4.
If x=-2, and y=-4, what is the value of 2x-(2x²-4y)
3 answers
you messed up in this step
= 2(-2) - [2(-2)² - 4(-4)]
= -4 - [2(4) - 16]
it should have been
= -4 - [2(4) + 16]
= 2(-2) - [2(-2)² - 4(-4)]
= -4 - [2(4) - 16]
it should have been
= -4 - [2(4) + 16]
I apologize for the mistake. Let's correct it:
2x - (2x² - 4y)
= 2(-2) - [2(-2)² - 4(-4)]
= -4 - [2(4) + 16]
= -4 - (8 + 16)
= -4 - 24
= -28
So, the correct value of 2x - (2x² - 4y) when x = -2 and y = -4 is -28. Thank you for pointing out the error.
2x - (2x² - 4y)
= 2(-2) - [2(-2)² - 4(-4)]
= -4 - [2(4) + 16]
= -4 - (8 + 16)
= -4 - 24
= -28
So, the correct value of 2x - (2x² - 4y) when x = -2 and y = -4 is -28. Thank you for pointing out the error.